2016
DOI: 10.1111/jnc.13684
|View full text |Cite
|
Sign up to set email alerts
|

The astrocytic response to the dopaminergic denervation of the striatum

Abstract: Increasing evidence suggests that the dopaminergic degeneration which characterizes Parkinson's disease starts in the striatal dopamine terminals and progresses retrogradely to the body of dopamine cells in the substantia nigra. The role of striatal astrocytes in the striatal initiation of the dopaminergic degeneration is little known. This work was aimed at studying the astrocytic response to the dopaminergic denervation of the striatum. The injection of 6-hydroxydopamine (25 μg) in the lateral ventricle of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 70 publications
1
38
0
1
Order By: Relevance
“…A recent study by Morales et al . () has suggested that occurrence of reactive astrocytosis needs the previous action of 6‐OHDA on dopaminergic neurons, in accord with the potentiation of LID by inflammagen LPS (Mulas et al ., ).…”
Section: Non‐neuronal Mechanisms Of Dyskinesia: Astrocytesmentioning
confidence: 77%
“…A recent study by Morales et al . () has suggested that occurrence of reactive astrocytosis needs the previous action of 6‐OHDA on dopaminergic neurons, in accord with the potentiation of LID by inflammagen LPS (Mulas et al ., ).…”
Section: Non‐neuronal Mechanisms Of Dyskinesia: Astrocytesmentioning
confidence: 77%
“…In a study by Tambuyzer et al [] shows that inhibition of microglia over‐activation may represent a therapeutic target in alleviating the progression of neurodegenerative diseases. Striatal reactive astrocyte during the dopaminergic denervation probably is the first stages of PD [Morales et al, ]. And inhibition of astrocyte activation is proposed as a strategy for the treatment of PD [Liu et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…; Morales et al . ). S100B was over‐expressed in crucial brain regions such as substantia nigra and striatum both in PD patients (Sathe et al .…”
Section: S100b As An Active Factor In Neural Injurymentioning
confidence: 97%
“…In the pathogenic mechanisms of PD, a crucial role has been indicated for activated pro-inflammatory astrocytes, also involving the overproduction and release of S100B, in response to striatal dopaminergic denervation or 6-hydroxydopamine administration Morales et al 2016). S100B was over-expressed in crucial brain regions such as substantia nigra and striatum both in PD patients (Sathe et al 2012;Rydbirk et al 2017) and in MPTP-treated mice (Sathe et al 2012;Viana et al 2016).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%